The legal regulatory framework for unfair risk allocation in oilfield service contracts in Malaysia - Wan Zahari, Wan Mohd Zulhafiz (2017)
Many oilfield service contracts in Malaysia contain an imbalanced allocation of liability and unfair indemnity and hold harmless clauses. Therefore, the legality of oilfield service contracts, and in particular the risk allocation provisions, will be explored and analysed in this study. It is also expected that the findings from this research will shed light on the problem concerning imbalanced risk allocation provisions and unfair indemnity and hold harmless clauses. Combining empirical evidence with legal doctrinal study, this research will propose a regulatory framework and practical measures to the Malaysian legislative body. Thus, a suitable legal mechanism will be proposed in order to solve this problem. The regulations are designed to address the issue of imbalanced risk allocation and unfair indemnity and hold harmless clauses between the operator and contractor in the oilfield service contracts in Malaysia. This study suggests a specific statutory law designed to regulate unfair risk allocation provisions and imbalanced indemnity and hold harmless clauses. The proposed law would seek to protect the interest of contractors in Malaysia and would be called: the Malaysian Oilfield Anti-Indemnity Act